2013
DOI: 10.1109/tnsre.2013.2249111
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Motor Imagery Brain-Computer Interface Based on Anodal Transcranial Direct Current Stimulation Modulation

Abstract: Abstract-Voluntarily modulating neural activity plays a key role in brain-computer interface (BCI). In general, the self-regulated neural activation patterns are used in the current BCI systems involving the repetitive trainings with feedback for an attempt to achieve a high-quality control performance. With the limitation posed by the training procedure in most BCI studies, the present work aims to investigate whether directly modulating the neural activity by using an external method could facilitate the BCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 38 publications
1
39
4
Order By: Relevance
“…Dieckhofer et al (2006) 1 0 9 A ,C -CP3 ? T0, T20 Kirimoto et al (2011/x2) 10 (x2) 15 (x2) A, C, S (x1)A, C (x1) -CP3 300 T0, T15À 20 N2 and P2 LEP amplitude Antal et al (2008) 1 0 1 5 A , C , S -Cz 40 T0 Terney et al (2008) 12 A,C, 7 S 15 C, S -Cz 40 T0 Csifcsak et al (2009) 1 0 1 0 A ,C ,S -Cz 40 T0 Mu/alpha ERD: motor imagery Matsumoto et al (2010) 6 10 A, C, S -C3 and surrounds n/a T0 Wei et al (2013) 8 A, 8 S 15 A, S -C3 and surrounds n/a T0 Lapenta et al (2013) 2 1 2 0 A ,C ,S -C3 and surrounds n/a T0…”
Section: Erp Discussionmentioning
confidence: 99%
“…Dieckhofer et al (2006) 1 0 9 A ,C -CP3 ? T0, T20 Kirimoto et al (2011/x2) 10 (x2) 15 (x2) A, C, S (x1)A, C (x1) -CP3 300 T0, T15À 20 N2 and P2 LEP amplitude Antal et al (2008) 1 0 1 5 A , C , S -Cz 40 T0 Terney et al (2008) 12 A,C, 7 S 15 C, S -Cz 40 T0 Csifcsak et al (2009) 1 0 1 0 A ,C ,S -Cz 40 T0 Mu/alpha ERD: motor imagery Matsumoto et al (2010) 6 10 A, C, S -C3 and surrounds n/a T0 Wei et al (2013) 8 A, 8 S 15 A, S -C3 and surrounds n/a T0 Lapenta et al (2013) 2 1 2 0 A ,C ,S -C3 and surrounds n/a T0…”
Section: Erp Discussionmentioning
confidence: 99%
“…Previous studies did not report the effect of tDCS on BCI task timing as timing was not variable [32,33]. For motor learning tasks examining the speed of performance, Nitsche et al [23] used a serial reaction time task with left M1 stimulation and right hand movement and found anodal subjects to have a decreased reaction time compared to cathodal and sham stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous electrophysiological studies found mixed effects on the ERD following tDCS stimulation. Initial MI work found an increase in ERD of the stimulated hemisphere (left M1) when performing MI [28,29] and MI-BCI [32] whereas others found no change in the ERD for MI, MI-BCI, or motor observation [30,33]. In our previous work [31], we found a decrease in beta ERD in the sensorimotor cortex of the stimulated hemisphere following HD-tDCS anodal stimulation as well as a trend towards increased ERD with cathodal stimulation, which we find here as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research suggests that users can learn to modulate their sensorimotor rhythm to issue control commands to physical devices [14]. Neural signals recorded using invasive, or to a limited degree, non-invasive, sense electronics can be processed for intent detection, and the outcome can be used for controlling external devices.…”
Section: Introductionmentioning
confidence: 99%